The impact of E-diaries and accelerometers on young adults' perceived and objectively assessed physical activity. (May 2017) - Eisenberg, Miriam H.; Phillips, L. Alison; Fowler, Lauren; Moore, Philip J.
Abstract: Objective: E-diaries and accelerometers promise more objective, real-time measurements of health behavior. However, social-psychological theory suggests that using electronic behavioral monitoring may influence rather than just record physical activity (PA), especially when a device is novel. Design: Participants (n = 146) were randomly assigned to either an accelerometer-only, e-diary-only, accelerometer + e-diary, or a no-technology control group for one week to assess how these technologies influenced PA, both perceived and actual, in young adults. Method: Participants reported their PA, overall and number of discrete exercise sessions (DES) at baseline and follow-up; accelerometers provided daily step counts and e-diaries captured daily reports of PA for the active week of the study. Results: Average daily steps in the accelerometer-only and accelerometer + e-diary groups did not differ nor did daily reports of PA via e-diary compared to accelerometer + e-diary group, showing that neither technology affected actual PA. ANCOVAS tested group differences in perceived PA; The accelerometer-only group had increased perceived overall PA but not DES compared to no-technology control. Conclusions: Accelerometers may increase perceived overall PA, but the tested technologies did not increase DES or actual PA, suggesting that they may be viable unbiased measures of PA. Highlights: Wearing an accelerometer daily increased perceived but not actual PA. The accelerometer group reported more perceived mild & moderate but not vigorous PA. Completing an e-diary daily did not change perceived or actual PA. Neither the e-diary nor the accelerometer changed reported discrete exercise sessions.